Burch technique in the treatment of urinary incontinence. - Novoa, Salomón (2015)
The author reviews 20-year experience with Burch procedure for treatment of stress urinary incontinence performed in 300 Chiclayo women with follow-up in 240. Most patients were over 40 years old and had had more than four deliveries. He obtained 87% cure rate and 13% failure rate. The author concludes that Burch procedure is easy to perform and is an excellent alternative in the treatment of stress urinary incontinence.